The Effect of Acupressure Therapy on Menstrual Pain Intensity - Siti Nabilah; Resi Galaupa (PT FORMOSA CENDEKIA GLOBAL, 2022)
Reproductive health of young women is not only a sexual problem but also involves all aspects of reproduction, including secondary sex development, which includes soft voice, enlarged breasts, enlargement of the hip area, and menarche. Therefore, this research aims to know the effect of acupressure therapy on the intensity of menstrual pain in female students at STIKes Yatsi Tangerang. This type of research is a quasi-experimental research that design isuses basedion igroup ipre-test iand ipost-test. iThe ipopulation iin ithis istudy iwas ia iLevel iII iMidwifery istudent iat iSTIKes iYatsi. Besides, the research was carried out in March 2022. Eventually, there is a change in menstrual pain in second-level female students at STIKes Yatsi before and after acupressure therapy.